The effect of physical activity on anxiety symptoms among children and adolescents with mental health disorders: a research brief - Anker, Ella Aase; Bøe Sture, Svanhild E.; Hystad, Sigurd William; Kodal, Arne (Frontiers in Psychiatry, 2024)
Background Anxiety is prevalent among children and adolescents (termed youths), and leads to reduced quality of life, disability, loss of education and reduced life-span. Physical activity has shown promising effects on symptoms of anxiety in adult populations, and an increasing amount of research has also demonstrated some effect in youth. However, physical activity is not widely used in youth mental health care, and research is very limited. Methods/design This single arm, pre-post study explores the effect of a manualized physical activity-based 14-session intervention termed Confident, Active and Happy Youth. Participants are youth attending specialized mental health care (N=51, M age = 13.4, SD = 2.2). Changes in anxiety symptoms are examined using mixed models with residual maximum likelihood (REML). The potential effect of anxiety subtype differences, participant age, comorbidity, and time spent in out-patient care are explored. Results Youths did not report any effect on anxiety symptoms after participation in CAHY, however, their parents report a significant reduction in youth’s anxiety symptoms in general (b = -0.11, 95%, CI: -0.21 to -0.01) and specifically for social phobia (b = -0.19, 95% CI: -0.35 to -0.03). Age and comorbidity showed no significant effect on anxiety symptoms post treatment. Prior treatment time in youth mental health care demonstrated inconclusive results. Conclusion The study finds initial evidence of symptomatic change in a clinical population of youth’s receiving a physical activity-based intervention. Our research provides preliminary support for physical activity as a supplementary treatment method for mental health disorders among youths. Clinical Trial Registration clinicaltrials.gov, NCT05049759